2022
DOI: 10.1002/htj.22574
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of flame stabilization methods in the premixed microcombustion of hydrogen–air mixture

Abstract: The premixed combustion of a lean hydrogen–air mixture is analyzed in this study to examine various properties and flame stabilization. A two‐dimensional (2D) analysis of a microscale combustor is performed with various shapes of bluff bodies (e.g., circular and triangular). Nine bluff bodies are placed at the entrance of the microscale combustor and solved with 2D governing equations. The analysis is performed with the three velocities of 10, 20, and 30 m/s, but the equivalence ratio is fixed in all cases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A testing campaign was conducted in order to validate the proper functioning of a newly developed afterburner. Starting from a geometry of the afterburner presented in the patent [9] and previously developed and validated for use with natural gas as fuel, a new flame holder geometry was developed and tested. Two flame holder prototypes were manufactured, one through classic manufacturing techniques (P1) and one using additive manufacturing (P2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A testing campaign was conducted in order to validate the proper functioning of a newly developed afterburner. Starting from a geometry of the afterburner presented in the patent [9] and previously developed and validated for use with natural gas as fuel, a new flame holder geometry was developed and tested. Two flame holder prototypes were manufactured, one through classic manufacturing techniques (P1) and one using additive manufacturing (P2).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that a recirculation zone was formed in the conventional bluff body (CBB) micro-combustor, while two symmetric recirculation zones were formed in the slotted bluff-body (SBB) micro-combustor and controllable slotted bluff-body (CSBB) micro-combustor. The premixed combustion of a lean hydrogen-air mixture was analyzed [9] to examine various properties and flame stabilization. A twodimensional (2D) analysis of a microscale combustor was performed with various shapes of bluff bodies (e.g., circular and triangular) to characterize the combined effects of the bluff body, such as shape, size, and blockage ratio, on micro-combustors, playing a crucial role in enhancing flame stability, efficiency, and blow-out limit.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the combustion performance, various studies have been conducted on these configurations at different velocities and equivalence ratios. For example, a study on flame stabilization with bluff body and wall cavity has shown significant improvement in combustion efficiency [13]. Kang et al investigated the flame stability limits and thermal performance of a parallel plate combustor with orthotropic wall made of pyrolytic graphite, which exhibits a high velocity limit due to improved temperature distribution on the plate [24].…”
Section: Sadatakhavi Et Al Conducted Experimental and Numerical Inves...mentioning
confidence: 99%
“…The inner recirculation zone enhances the mixing through swirl-like configurations and becomes effective in evaporating fuel, while the combustion becomes efficient due to the recirculation zone around the linear wall. In their investigation into flame stabilization, Jha et al explored several different factors, ultimately determining that using a bluff body is one of the most effective methods to stabilize flames [13]. The study was focused on optimizing geometry-based parameters to gain a better understanding of how to stabilize flames in narrow channels.…”
Section: Numerical Studies On Micro Combustorsmentioning
confidence: 99%
See 1 more Smart Citation